Telemedicine and Telementoring in Urology: A Glimpse of the Past and a Leap Into the Future - Ayoub, Christian Habib; El-Asmar, Jose M.; Abdulfattah, Suhaib; El-Hajj, Albert (Frontiers in Surgery, 2022)
Telemedicine is the process of utilizing telecommunications and digital relay to perform, teach, or share medical knowledge. The digital era eased the incorporation of telemedicine to different areas of medical care, including the surgical care of Urologic patient mainly through telementoring, telesurgery, and telerobotics. Over the years, Telemedicine has played an integral part in a physicians’ ability to provide high quality medical care to remote patients, as well as serve as an educational tool for trainee physicians, in the form of telementoring. During the COVID-19 pandemic, telemedicine has played a vital role in combatting the health implications of confinements. Challenges of telemedicine implementation include cost, ethical considerations, security, bandwidth, latency, legal, and licensure difficulties. Nevertheless, the future of telemedicine, specifically telementoring, promises several improvements and innovative advancements that aim to bridge the gap in technological divides of urologic care. In this review, we build on what is already known about telemedicine focusing specifically on aspects related to telementoring, telestration, and telesurgery. Furthermore, we discuss its historical role in healthcare with a special emphasis on current and future use in urology.